Eksistensi Hukum Ekonomi Syariah Dalam Hukum Perdata - Maulana Ira M. Irsyad Arifin (Program Pascasarjana IAIN Langsa, 2021)
The history of the positiveization of Islamic civil law was carried out by the Ottoman Government in enforcing the Islamic Civil Code which consisted of 1851 articles. On the other hand, the